The Effect of Naftalene Acetic Acid and Benzyl Amino Purine on Growth of Potato Planlets In Vitro - Nurmufiidah, Rahma; Kusmiyati, Florentina; Lukiwati, Dwi Retno (Journal of Tropical Crop Science and Technology, 2020)
The purpose of this research was to analyze the effect of Naftalene Acetic Acid (NAA) and Benzyl Amino Purine (BAP) on growth of potato plantlet (Solanum tuberosum L.). This research used factorial Completely Randomized Design (CRD). The first factor was the concentration levels of NAA (A1 = 0,5 ppm A2 = 1.5 ppm and A3 = 2.5 ppm). The second factor was the concentration levels of BAP (B1 = 1 ppm B2 = 2 ppm and B3 = 3 ppm). Parameter observed were number of nodes, number of branches, number of roots, percentage of life explants, and percentage of damaged explants. Data were analyzed with analysis of variance and continued by Least Significance Different (LSD). The results showed that NAA 0.5 ppm increased the number of nodes, branches, and  roots compared to other treatments. The concentration of BAP 1 ppm increased the number of roots compared to other treatments. The concentration of NAA 0.5 ppm and BAP 1 ppm showed the best percentage of life explants (100 %) and showed the minimum percentage of damaged explants (0 %).